Toward a Critical-PBL: Centering a Critical Consciousness in the Middle Grades - Jaclyn Caires-Hurley; Margarita Jimenez-Silva; Rachel Harrington (Middle Grades Review, 2020)
The dual pandemic of 2020 that includes racism and COVID-19 demonstrates the need for students to become socially responsible and critically conscious world citizens. Students in the middle grades are developing their sense of identity while concomitantly trying to understand the complex world around them. While many teachers understand the need for critical pedagogy, many still struggle to find time to teach rigorous content standards while integrating social justice education. In this article, we propose the four pillars of Critical-Problem Based Learning (Critical-PBL). Using critical standards, critical problems, critical content, and critical discourse, we offer a framework to support teachers in creating a space for students to learn how to name injustices and work toward social transformation.
Keywords: Critical Pedagogy; Problem-Based Learning; Criticality; Teacher Education; Middle School; Middle Grades